The Routledge handbook of trust and philosophy - Simon, Judith (London : Routledge, 2020)
Trust is pervasive in our lives. Both our simplest actions - like buying a coffee, or crossing the street - as well as the functions of large collective institutions - like those of corporations and nation states - would not be possible without it. Yet only in the last several decades has trust started to receive focused attention from philosophers as a specific topic of investigation. The Routledge Handbook of Trust and Philosophy brings together 31 never-before published chapters, accessible for both students and researchers, created to cover the most salient topics in the various theories of trust. The Handbook is broken up into three sections: I. What is Trust? II. Whom to Trust? III. Trust in Knowledge, Science, and Technology The Handbook is preceded by a foreword by Maria Baghramian, an introduction by volume editor Judith Simon, and each chapter includes a bibliography and cross-references to other entries in the volume.
OCLC-licensed vendor bibliographic record.
Keywords: Trust -- Handbooks, manuals, etc; PHILOSOPHY / General